Assessing UK trade policy readiness - David Henig (European Centre for International Political Economy (ECIPE), 2018)
In leaving the European Union the UK will conduct a fully independent trade policy for the first time since January 1973. This independent trade policy may come into force gradually, with an Implementation Period from March 2019 to December 2020 seeing the UK in a continuing Customs Union with the EU, prior to having full control and the freedom to implement new Free Trade Agreements (FTAs) from January 2021. This paper will assess the UK's readiness to successfully run a fully independent trade policy. In the next section we define a measurement framework based around six pillars we have observed as being crucial to success globally. These are not the specifics of which agreements or policies should be pursued, but rather a set of criteria that reflect whether a country has a sufficient and realistic understanding of their priorities and constraints in implementing a trade policy. We then consider how the UK is currently performing against these criteria, accepting that one would expect this to be to a degree a work in progress. However, this analysis should inform the priorities for future work.
Keywords: 330